THE PHYSICS AND ELECTRONICS OF HUMAN CONSCIOUSNESS, MIND AND THEIR FUNCTIONS. - Ramabrahmam, Varanasi (Cosmos & History, 2019)
Human consciousness, the result of breathing process as dealt with in the Upanishads, is translated into modern scientific terms and modeled as a mechanical oscillator of infrasonic frequency. The bio-mechanic oscillator is also proposed as the source of psychic energy. This is further advanced to get an insight of human consciousness (the being of mind) and functions of mind (the becoming of mind) in terms of psychic energy and reversible transformation of its virtual reflection. An alternative analytical insight of human consciousness and mental functions to other theoretical approaches is developed based on Upanishadic insight and presented. That reversible transformation of virtual psychic energy reflection termed as maya, creating various consequential / parallel / simultaneous conscious-states, phases, cognitive and communicative states, modes of language acquisition and communication, and kinds of function of human mind is visualized. The concept is extended to delineate form, structure and functional mechanism of human mind and to know how it facilitates human mental acquisitions, retentions, communications, including language abilities. This proposal is extensively discussed and the hardware and software of mind as envisaged in Indian philosophical systems are put forward. All this presentation is translated to neurobiology in terms of brain wave modulation / demodulation terms. Also a preliminary proposition of physic-chemical nature of human thoughts and ideas is given.